Fra bakteriernes perspektiv. Positioner i forholdet mellem litteratur og naturvidenskab belyst gennem Mark Twains “3,000 Years Among the Microbes” og Christian Böks “The Xenotext Experiment” - Jørgensen, Jens Lohfert (Passage - Tidsskrift for litteratur og kritik, 2018)
Jens Lohfert Jørgensen: “From the Perspective of Bacteria. Position in the Relationship Between Literature and Science Illustrated by Mark Twain’s 3,000 Years Among the Microbes and Christian Bök’s The Xenotext Experiment” This article discusses how literature administers scientific notions about bacteria based on two curious examples: Mark Twain’s uncompleted novel 3,000 Years Among the Microbes (1905) and the Canadian experimental poet Christian Bök’s work The Xenotext Experiment (2007-). There are some noteworthy correspondences between the works’ engagement with bacteria: They both attempt to establish a microbial perspective (Twain by using a cholera bacterium as narrator, Bök by trying to make a bacterium produce a poem), they both use this engagement to experiment with literary form, and they are both closely related to the natural sciences. On the backdrop of these correspondences, the article sketches out a typology of five modal positions in the relationship between literature and science: Mediating, satirical, allegorical, ontological, ludic. The typology has a local character, but can form a starting point of the discussion of further modal positions.